2014
DOI: 10.1093/jisesa/ieu158
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Classification and Environmental Interpretation of Secondary Forests 18 Years After the Invasion of Pine Forests by Bursaphelenchus xylophilus (Nematoda: Aphelenchoididae) in China

Abstract: With growing concerns over the serious ecological problems in pine forests ( Pinus massoniana , P. thunbergii ) caused by the invasion of Bursaphelenchus xylophilus (the pine wood nematode), a particular challenge is to determine the succession and restoration of damaged pine forests in Asia. We used two-way indicator species analysis and canonical correlation analysis for the hierarchical classification of existing secondary forests that have been restored since the invasion of B. xylophilus 18 years ago. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The correlation between parasitic insects and woody plant species indicated that broad-leaved tree species may provide more resources and ecological niches for parasitic insects. This result is consistent with a previous study showing that the number and diversity index of parasitic insects increased with an increase in the proportion of broad-leaved tree species in a coniferous forest ecosystem in Zhejiang Province (Wang et al, 2014). According to "Resource Concentration Hypothesis," the increase in plant species diversity can provide more habitats and food resources, which may significantly affect the structure of insect functional groups and increase the species and individual numbers of herbivorous and parasitic insects (Gao et al,2013(Gao et al, , 2018Knops et al, 1999;Root, 1973;Taki et al, 2010).…”
Section: Number Of Individualssupporting
confidence: 93%
See 1 more Smart Citation
“…The correlation between parasitic insects and woody plant species indicated that broad-leaved tree species may provide more resources and ecological niches for parasitic insects. This result is consistent with a previous study showing that the number and diversity index of parasitic insects increased with an increase in the proportion of broad-leaved tree species in a coniferous forest ecosystem in Zhejiang Province (Wang et al, 2014). According to "Resource Concentration Hypothesis," the increase in plant species diversity can provide more habitats and food resources, which may significantly affect the structure of insect functional groups and increase the species and individual numbers of herbivorous and parasitic insects (Gao et al,2013(Gao et al, , 2018Knops et al, 1999;Root, 1973;Taki et al, 2010).…”
Section: Number Of Individualssupporting
confidence: 93%
“…Similar results were found in many previous studies, which showed that the invasion of B. xylophilus can lead to the succession of the pure P. massoniana forest ecosystem into a mixed coniferous and broadleaf forest ecosystem or even a broadleaf forest ecosystem (Gao et al, 2015;Shi et al, 2007;Wang et al, 2014). By comparing and analyzing the niche indices of the main woody plant species, the vegetation communities in the woody plant layer did not degenerate in the direction of the shrub layer after the invasion of the Masson pine ecosystem by B. xylophilus.…”
Section: Number Of Individualssupporting
confidence: 91%
“…The red and yellow soil areas of the Yangtze River Basin are facing serious soil erosion and poor soil conditions [15]. PWD damages the forest coverage, forest quality, and land productivity; these factors are difficult to restore, and their destruction easily leads to soil erosion and causes mudslides, mountain torrents, and many ecological disasters [16]. PWD epidemics have been found in important ecological locations, such as the Three Gorges Reservoir area, Qinba Mountain, Zhangjiajie, Lushan, Qiandao Lake, and many key national scenic spots [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since first invaded Nanjing, Jiangsu, China in 1982, PWD has caused immense damage to forest resources and ecosystems in 18 provinces of China ( Ye 2019 ). The pinewood nematode is almost exclusively associated with its symbiont, a pine sawyer beetle Monochamus alternatus ( Linit 1988 , Wang et al 2014 ). The geographic distribution of M. alternatus partly determines the invasive fate of the nematode population and epidemiology of PWD.…”
mentioning
confidence: 99%